B because for it to be a function one X value cant have more than one Y value and B is the only one that follows the rule
Answer:
Below
Step-by-step explanation:
Substituting the given values:
f(6) = 6(2/3) - 2 = cube root of 6^2 - 2 = cube root 36 - 2
f(-6)= (-6)(2/3) - 2 = cube root of(-6)^2 - 2 = cube root 36 - 2
So This is true,
f(6) = cube root of 6^2 - 2 = cube root 36 - 2 = 1.3019
2 * f(3) = 2 * (cube root of 3^2 - 2 ) = 2 * (cube root of 9 - 2) = 0.1602
So False,
Answer:
important, valuable, nice,
The worng answer is [b]
hope this helps you
have a great day
It’s 16
You would multiply height (4) by the base (length(2) x width(2)=4) which is 16